High performance eco-friendly free abrasive machining using an additively fabricated tool and PCD based slurry - Dawid Zieliński; Mariusz Deja; Wit Grzesik; Krzysztof Żak (Scientific Reports)
Abstract This paper presents the results from lapping experiments conducted with the use of a lapping plate fabricated by the selective laser sintering (SLS) from the polyamide PA2200 powder. The minimum quantity of diamond grains (grade D107) and paste (grade SD 28/20) were uniformly distributed on the active surface of a soft plate allowing for the effective material removal and a substantial improvement of the surface finish of Al2O3 ceramic samples. The assessment of statistically significant differences between the means of the technological effects confirmed the stable course of lapping. Obtained results were compared to the results from lapping using other abrasive tools. It was demonstrated that selective laser sintering can be utilized to fabricate tools for the cheap, effective and environment-friendly abrasive finishing processing with minimum quantity abrasive dosing (MQAD).